Objections to Hadith Based on Allegations of Qur’anic Distortion: An Analytical and Critical Study - Dr. Hafiz Muhammad Hassan; Sadia Shabbir; Ayesha Shabbir Ahmed (Journal of Religion and Society, 2025)
The Qur'an is the primary source of Islam and the fountainhead of guidance, which has remained preserved in its original form since the time of its revelation. There is a consensus among the Muslim Ummah that the Qur'an is the divine word of Allah, revealed verbatim to the Prophet Muhammad (peace be upon him) and meticulously compiled through the efforts of his noble Companions. However, throughout history, some Orientalists, deviant sects, and critics of the Qur'an’s historical authenticity have attempted to cast doubts on its preservation and integrity. Among these, certain objections are directed towards hadith literature, in which there appear to be some narrations that are interpreted as evidence for the alleged distortion of the Qur'an.These objections generally stem from narrations that mention the abrogation or loss of certain words, verses, or chapters of the Qur'an, or refer to differences in recitation (qira’at) among the Companions. Orientalists and some Shiite scholars, along with controversial exegetical interpretations, have used such narrations to argue that the hadith corpus contains traces of Qur'anic distortion. These claims not only challenge the established belief in the Qur'an’s preservation but also raise questions about the authenticity and authority of hadith literature.This study aims to present a scholarly and critical analysis of these objections. For this purpose, the various types of relevant hadiths, their chains of transmission, and their texts will be thoroughly examined. Furthermore, the narrations will be analyzed in their proper context, in light of the principles of hadith science and the views of renowned hadith scholars. The study will also demonstrate how the allegations of Qur'anic distortion are unfounded, contextually misinterpreted, and contrary to sound scholarly methodology. The ultimate objective of this inquiry is to defend the hadith corpus with critical insight and to provide rational and textual evidence for the Qur'an’s immaculate preservation. Keywords: Objections to Hadith, Allegations of Qur'anic, Fountainhead, Muslim Ummah, Orientalists, Interpretations, Demonstrate